DIAGNOSTIC IMPORTANCE OF BONE MARROW EXAMINATION IN HAEMATOLOGICAL MALIGNANT AND NON-MALIGNANT DISORDERS - Gandapur, Abdus Salam Khan; Nadeem, Seema; Riaz, Mariam; Mannan, Modood ul (Journal of Ayub Medical College Abbottabad, 2015)
Background: Bone marrow examination is regarded as one of the most important diagnostic procedure to assess various haematological disorders. The uses and advantages of bone marrow aspiration are numerous. This study was conducted with the aim to evaluate the frequency of involvement of bone marrow with malignant and non-malignant haematological and other clinical disorders and to observe the significance of bone marrow in establishing primary diagnosis of the same condition. Methods: This was descriptive carried out at the Department of Pathology, Women Medical College, Abbottabad. A total of 570 successful bone marrow examinations were performed. Patients of all age groups and genders were included in the study. After history, clinical examination and blood complete counts, bone marrow was aspirated from posterior superior iliac spine, sternum or tibia. Smears were made, stained and examined under microscope. Results: Total numbers of cases were 570. Ages ranged from 6 months to 70 years. Male to female ratio was 2:1. The common clinical presentation for bone marrow examination were progressive pallor, fever of unknown origin and bleeding. Total numbers of non-malignant haematological conditions were 417 (73.2%) while the numbers of malignant conditions were 153 (27.8%). Conclusion: Bone marrow examination remains a simple, reliable and effective technique in the diagnosis of many important clinical conditions. It is a reliable accessible tool for diagnosing various haematological malignant and non-haematological conditions. The importance of bone marrow examination is further highlighted in cases where routine investigations fail to reach a conclusive diagnosis. Treatable conditions like visceral leishmaniasis and malaria are diagnosed and the result is decreased mortality from these diseases.